Wide Band CPW Fed Slotted Microstrip Antenna - Pawan Kumar; Malay Ranjan Tripathy; H.P. Sinha (Institute of Advanced Engineering and Science, 2015)
In this paper, a design of compact coplanar waveguide fed UWB slot antenna is presented. The proposed antenna has simple structure consisting rectangular slot with uneven coplanar ground structures. The proposed antenna structure is investigated by using MoM based electromagnetic solver IE3D. The simulation and measured results show that the antenna offers performance for wideband system from 4.5 GHz to11.8 GHz with return loss better than -10dB over the frequency spectrum with VSWR less than 2.5. The antenna configuration would be quiet useful for indoor applications. The antenna is fabricated and simulated. Measured results show a good agreement with simulated results. DOI: http://dx.doi.org/10.11591/telkomnika.v15i1.8078